2003
DOI: 10.1159/000070994
|View full text |Cite
|
Sign up to set email alerts
|

Effluent CA 125 Concentration in Chronic Peritoneal Dialysis Patients: Influence of PD Duration, Peritoneal Transport and PD Regimen

Abstract: In terms of the integrity of the peritoneal membrane in peritoneal dialysis (PD), the peritoneal mesothelial cells play a pivotal role since its monolayer constitutes the first line of the peritoneal membrane. Cancer antigen 125 (CA 125) is released by peritoneal mesothelial cells and correlates with the mesothelial cell mass in PD. Since its effluent concentration is easy to determine in chronic PD patients, CA 125 serves as an in vivo marker of biocompatibility. We performed a cross-sectional study to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 13 publications
2
12
1
Order By: Relevance
“…Table 4 lists the common tumor markers and their efficacy in dialysis patients. Cancer antigen 125 is a tumor marker for ovarian cancer but is also produced by mesothelial cells (34) and has been reported to be a functional marker for mesothelial cell mass and transport characteristics in patients who are on peritoneal dialysis (35). However, cancer antigen 125 is less useful as a tumor marker in dialysis patients because any serosal fluid (pleural effusion, ascites, etc.)…”
Section: Tumor Markers In Dialysis Patientsmentioning
confidence: 99%
“…Table 4 lists the common tumor markers and their efficacy in dialysis patients. Cancer antigen 125 is a tumor marker for ovarian cancer but is also produced by mesothelial cells (34) and has been reported to be a functional marker for mesothelial cell mass and transport characteristics in patients who are on peritoneal dialysis (35). However, cancer antigen 125 is less useful as a tumor marker in dialysis patients because any serosal fluid (pleural effusion, ascites, etc.)…”
Section: Tumor Markers In Dialysis Patientsmentioning
confidence: 99%
“…Dialysate CA125 levels at the 4th hour ranged between 9 and 65 U/ml, and AR CA125 values were 108-471 U/min/1.73 m 2 [4,13,15,16,17,18,19,20,21]. In all the above-mentioned cross-sectional investigations and also in ours, determination of CA125 a Relation between the stable group and the peritonitis group b Relation between the peritonitis group and the recovery group c Relation between the stable group and the recovery group Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of cross-sectional studies found no relationship between AR CA125 and age in adults [18,20] or in children [9]. Only one adult study reported a positive correlation between age and AR CA125 levels after correction of these values with body surface area [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, none of the conventionally applied PD fluids are entirely biocompatible with respect to toxic effects exerted on cellular and extracellular structures of the peritoneal membrane. During APD with frequent and short dwell times of 0.5-3.0 h, the adverse effects of conventional PD solutions administered freshly during each cycle may accumulate much more over treatment time than during the long dwell periods with CAPD treatment [47,48]. Early biocompatibility studies on peritoneal host defense status comparing patients on long-term CAPD and continuous cyclic PD (CCPD) showed no significant differences with respect to macrophage function or effluent opsonic activity when treatment times were equal [49].…”
Section: Biocompatible Pd Fluids For Pdmentioning
confidence: 99%